2021
DOI: 10.3389/fimmu.2021.682948
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Immune System Regulation and Type 1 Diabetes: Cell-to-Cell Communication Mediators, Disease Biomarkers, and Promising Therapeutic Tools

Abstract: Extracellular vesicles (EVs) are generated by cells of origin through complex molecular mechanisms and released into extracellular environment. Hence, the presence of EVs has been described in multiple biological fluids and in most cases their molecular cargo, which includes non-coding RNAs (ncRNA), messenger RNAs (mRNA), and proteins, has been reported to modulate distinct biological processes. EVs release and their molecular cargo have been demonstrated to be altered in multiple diseases, including autoimmun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 194 publications
(265 reference statements)
0
22
0
Order By: Relevance
“…The pivotal role of EVs was identified in a variety of diseases and pathogenetic mechanisms ( Grieco et al, 2021 ). Considering the lipid envelops structure and cargo-delivery ability, EVs were involved in cell-to-cell communication of different cell types ( Sanwlani and Gangoda, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The pivotal role of EVs was identified in a variety of diseases and pathogenetic mechanisms ( Grieco et al, 2021 ). Considering the lipid envelops structure and cargo-delivery ability, EVs were involved in cell-to-cell communication of different cell types ( Sanwlani and Gangoda, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…By example, in prostate cancer, urinary EVs have been shown to carry RNAs that serve as signatures of disease outcomes [ 139 ]. Similarly, in T1D, diverse components of β cell-derived EVs, including miRNA, DNA, protein, and metabolites have been identified [ 140 , 141 ]. It is reported that rat and human pancreatic β cells under inflammatory stress release EVs containing GAD65, IA2, and proinsulin that can subsequently can activate dendritic cells and propagate adaptive immunity [ 142 ].…”
Section: Extracellular Vesicle Components As Potential T1d Biomarkersmentioning
confidence: 99%
“…25À29 Circulating miRNAs have been detected in different human biofluids including plasma, serum, urine, breast milk, cerebrospinal fluid and saliva. 30 In biofluids, miRNAs and others small RNA species are complexed with multiple components including extracellular vesicles 31,32 and/or ribonucleoproteins (eg, Argo-naute2), 33 thus conferring them a high degree of stability and resistance to ribonucleases. 34,35 In T2D, many efforts have been made to identify a series of circulating miRNAs as predictive, diagnostic and/or prognostic disease biomarkers.…”
Section: Introductionmentioning
confidence: 99%